The impact of a preoperative evaluation process on weight reduction and glycemic control in patients undergoing bariatric and metabolic surgery - Jennifer Tempany; Andrew Collier; Abdulmajid Ali (Wiley, 2024)
Abstract Introduction Metabolic surgery is a sustainable intervention for obesity and type 2 diabetes. Preoperative education optimizes weight loss and glycemic control outcomes. Objective This study aimed to determine the effect of a generalized preoperative evaluation process (PEP) in patients who underwent bariatric surgery on weight loss and glycemic control pre‐ and post‐surgery. Methods Data were retrospectively collected and analyzed for patients with type 2 diabetes who underwent bariatric surgery between 2010 and 2016. Patients were categorized into two groups determined by participation in the PEP. The groups were named the PEP group and non‐PEP group. The correlation among engagement in the PEP was determined using the chi‐square test and t‐test. Statistical analysis with p < 0.05 was deemed significant. Results 129 patients were included in the study; 86 females (67%) and 43 males (33%). Fifty‐nine patients (46%) engaged in the PEP and 70 (54%) patients did not engage in the PEP. A greater reduction in weight loss was observed in the PEP group versus the non‐PEP group from initial enrollment to pre‐surgery (14.3 ± 9.2 kg vs. 11.6 ± 9.2 kg; p = 0.11), and from pre‐surgery to 2‐years post‐surgery (20.6 ± 14.8 kg vs. 16.9 ± 15.6 kg; p = 0.17). A greater reduction in HbA1c from initial enrollment to pre‐surgery was seen in the PEP group versus the non‐PEP group (0.90 ± 1.28% vs. 0.63 ± 1.07%); however, this was not maintained from pre‐surgery to 2‐year post‐surgery (0.51 ± 1.18% vs. 0.70 ± 1.73%). In both cases, the statistical difference was insignificant. Conclusion The PEP was not associated with improvements in short‐term weight loss or glycemic control pre‐surgery and a 2‐years post‐surgery. Patients may benefit from individually tailored preoperative weight management strategies.